Studies on double selenates. XI. Thermal decomposition of lanthanides of the ceric group and lithium double selenates - Cruz, P. M. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Ionashiro, Massao [UNESP]; Giolito, I. (Elsevier B.V., 1990)
A previous communication [1] described the preparation of the double selenates of lanthanum and the alkali metals; the La-Li compound has the formula La2(SeO4)3 · Li2SeO4 · 8H2O. Subsequent reports [2-4] have shown that it was not possible to prepare the Ce-Li, Pr-Li, Nd-Li and Sm-Li double selenates, using the same method [1]. It was possible to isolate the double selenates of all the cerie group lanthanides and lithium not previously described and, also, a La-Li double selenate having a different stoichiometry, using a modified preparation technique. © 1990.